Dihydrophenazine‐Based Conjugated Microporous Polymer Cathodes with Enhanced Electronic and Ionic Conductivities for High‐Performance Aluminum Dual‐Ion Batteries. Issue 3 (5th December 2022) - Ma, Wenyan; Luo, Lian‐Wei; Huang, Xiuhua; Dong, Peihua; Chen, Yu; Zhang, Chong; Huang, Fei; Jiang, Jia‐Xing; Cao, Yong
Abstract: It is fundamentally challenging for cathode materials to achieve long life, high capacity, and fast kinetics in rechargeable aluminum batteries, due to the strong electrostatic interaction between Al 3+ and the host materials. Herein, the redox‐active dihydrophenazine (Pz) is coupled with pyrene (Py) or biphenyl (Ph) to develop two conjugated microporous polymers of PyPz and PhPz as AlCl4 − ‐hosting cathodes for aluminum dual‐ion batteries (ADIBs). It is revealed that the planar Py unit endows PyPz with an extended conjugated skeleton and a higher surface area than PhPz produced from the Ph unit with a twisted structure, thus leading to a higher redox activity for PyPz. Hence, the PyPz cathode delivers a much higher capacity of 231 mAh g −1 than PhPz (137 mAh g −1 ). Its porous structure and insolubility also ensure PyPz shows a superior rate performance and exceptional cyclability over 100 000 cycles. Meanwhile, the feature of fast kinetics for AlCl4 − storage also allows PyPz to operate well at not only a low temperature (−30 °C) but also a high areal capacity of 2.53 mAh cm −2 . These findings suggest that redox‐active conjugated polymers are promising advanced organic cathodes for sustainable ADIBs, where the electrochemical performance can be significantly enhanced by rational structural design. Abstract : Redox‐active dihydrophenazine and pyrene are selected to construct a conjugated microporous polymer (PyPz) as the cathode material for aluminum dual‐ion batteries. The cross‐linked structure and enhanced conjugation lead to high ionic and electronic conductivities for PyPz, which enable PyPz to realize excellent electrochemical performance including high capacity (231 mAh g −1 ) and outstanding rate capability and more than 100 000 cycles.